2016
DOI: 10.1111/jnc.13840
|View full text |Cite
|
Sign up to set email alerts
|

Imaging mass spectrometry reveals loss of polyunsaturated cardiolipins in the cortical contusion, hippocampus, and thalamus after traumatic brain injury

Abstract: Traumatic brain injury (TBI) leads to changes in ion fluxes, alterations in mitochondrial function and increased generation of reactive oxygen species, resulting in secondary tissue damage. Mitochondria play important signaling roles in coordination of multiple metabolic platforms in addition to their well-known role in bioenergetics. Mitochondrial signaling strongly depends on cardiolipin (CL), a mitochondria-specific structurally unusual anionic phospholipid containing four fatty acyl chains. While our previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 104 publications
(113 reference statements)
3
57
0
Order By: Relevance
“…This enhancement of CL signals from EDC/PLC tissue treatment is consistent with our previous results with MALDI imaging. 9,10 Recently, Angerer et al have shown that frozen hydrated tissue and dried tissue exposed to various reactive vapors aids in the analysis of brain lipids by TOF-SIMS. Enhanced high-mass species were observed, but no CL species were reported in that study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This enhancement of CL signals from EDC/PLC tissue treatment is consistent with our previous results with MALDI imaging. 9,10 Recently, Angerer et al have shown that frozen hydrated tissue and dried tissue exposed to various reactive vapors aids in the analysis of brain lipids by TOF-SIMS. Enhanced high-mass species were observed, but no CL species were reported in that study.…”
Section: Resultsmentioning
confidence: 99%
“…However, since our previous studies indicated that the tissue treatment protocol enhanced the signals for gangliosides in MALDI imaging, 9,10 we examined the higher mass region for indications of them by GCIB-SIMS. 9,10 Interestingly, signals for several brain ganglioside species were also enhanced by EDC/PLC treatment (Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney sections for high spatial resolution analysis were coated with 40 mg/ml DHB in 50 % methanol using a TM Imaging Sprayer (HTX Technologies). Brain and lung sections were coated with DHB as a 0.5 M solution in 2:1 chloroform (HPLC grade, Sigma-Aldrich) to methanol (LC/MS grade, ThermoFisher Scientific) according to our previously published protocol (Sparvero et al, 2016). In brief, the matrix solution was loaded into a capillary-sprayer aerosol device.…”
Section: Star Methods Textmentioning
confidence: 99%
“…Lung images were acquired at 50 μm lateral resolution in both positive and negative polarity, brain in positive polarity at 200 μm, and kidney in positive polarity at 5 μm. MALDI-MS images from Bruker instruments were produced using FlexImaging 4.0 software (Bruker Daltonics), and those from the AB Sciex with MSI Reader v0.06 software (www.msireader.com) using our previously published protocol (Sparvero et al, 2016). Heat maps for a given mass/charge ( m / z ) value ± 0.25 Da were generated either as a rainbow display (for single species) or red/green (for co-localization of two different species).…”
Section: Star Methods Textmentioning
confidence: 99%